2022
DOI: 10.1177/26318318211065648
|View full text |Cite
|
Sign up to set email alerts
|

Internet Pornography Use Among Medical Students in India: Extent and Effect

Abstract: Background: Medical students are more susceptible to stress associated with long working hours, arduous studies, and living alone away from the home, which may affect their psychological well-being. They may indulge in the use of internet and pornography to ameliorate their stress. Internet is one of the main sources of pornographic content as it is easily available, affordable, and accessible. Objective: The current study seeks to quantitatively estimate the extent of internet addiction and pornography use am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…A. Wéry et al [7] 2014 in Canada, evoked a predominance of the disorder in two-thirds of men. The same is true with Kumar et al [12] 2022 in India, who reported a male predominance of 68%. A similarly high prevalence of addiction to cybersexuality was reported by Satyanaraya et al [18] 2021 in India and by Beutel et al [16] 2017 in Germany.…”
Section: Gendersupporting
confidence: 77%
See 1 more Smart Citation
“…A. Wéry et al [7] 2014 in Canada, evoked a predominance of the disorder in two-thirds of men. The same is true with Kumar et al [12] 2022 in India, who reported a male predominance of 68%. A similarly high prevalence of addiction to cybersexuality was reported by Satyanaraya et al [18] 2021 in India and by Beutel et al [16] 2017 in Germany.…”
Section: Gendersupporting
confidence: 77%
“…Several other authors have reported a similar prevalence. These include Vipin K et al [12] in India in 2022, who found a prevalence of 11% in a population of medical students, R. Ballester et al [13] (10.8%) in a population of Spanish teenagers in 2015, Giordano et al [6] who found a prevalence of 10.3% in a population of schoolchildren in the USA in 2017, and V. Cordonnier et al [14] (10%)…”
Section: Prevalence Of Cybersex Addictionmentioning
confidence: 99%
“…For example, 67.5% of 16–24-year-olds from urban areas of Pakistan reported regularly viewing pornographic content [ 39 ]. This rate compares with another recent Asian subcontinent study from India in which 54% of respondents reported Internet pornography use, 11% of whom were problematic users [ 42 ], and also with a recent Malaysian study on college students that found that over 74%—mostly males—reported regular exposure to pornography [ 43 ].…”
Section: Context Rationale and Aimssupporting
confidence: 50%
“…Another study in Bangladesh found around 58.4% of undergraduate students were highly involved with PPU [21]. Studies in India suggest a concerning prevalence of PPU among medical students, with estimates ranging from 11% [22] to 12.5% [23]. PPU may contribute to depression in people who are addicted, can disrupt real-life relationships, leading to social isolation, and may contribute to mood disorders [24,25].…”
Section: Introductionmentioning
confidence: 99%